Refinements of spectral resolutions and modelling of operators in II1 factors - Massey, Pedro Gustavo (2008)
We study refinements between spectral resolutions in an arbitrary II1 factor M and obtain diffuse (maximal) refinements of spectral resolutions. We construct models of operators with respect to diffuse spectral resolutions. As an application we obtain new characterizations of sub-majorization and spectral preorder between positive operators in M and new versions of some known inequalities involving these preorders.